THE PHENOMENON OF LOVE IN THE MENTAL REFLECTION OF THE CONTEMPORARY SOCIAL TOPICS - L. V. Shabanov; L. V. Smetankina; S. V. Lychagina (Вестник Кемеровского государственного университета, 2016)
The purpose of the paper is to consider the modern concept of love (in the framework of the social psychology of the “Man and Woman” relations), reflecting the specificity of scientific approaches in our century. The authors refer to the phenomenon of love in the history of the humanity, which is transformed into a new archetypal reality through global and socio-cultural changes. By method of comparative analysis the authors attempted to trace the dynamics of changes of the rhythm and way of life, reflected in the framework of changes in social relations within the communication space of “male” and “female”, the similarities and differences of this. The authors make a conclusion about the archetypes associated with the conversion of love in consummation of external manifestations. Schematically this process looks like the desire for functional infantilisation of generations that extends in the framework of “birth - death – rebirth” through the archetypal theme of “child” and “hero”; however, individuation (narcissism) leads to a loss of subjectity and the updated archetypal theme of “the disabled hero” is compensated in the image of “anti-love”.